1001 Surgical Escape Rooms: A Novel Approach for Teaching Surgical Skills. (19th August 2022) - Thakkar, R; Wharf, O; Hanson, M; Badenoch, T; Hunter, I; Bamford, R; Cooper, S
Abstract: Aim: Traditional classroom-based teaching of surgical skills has been used commonly in the past. Although, use of an escape room is a new form of a practical teaching method to deliver surgical skills teaching. We compared and assessed effectiveness of the traditional classroom teaching versus practical escape room teaching of the basic surgical skills. Method: Two teaching sessions were delivered to third year medical students. Each session consisted of two groups and two sessions. Each group received either the classroom-based teaching or the escape room teaching, then switching over to the other teaching. Each student was asked to complete a questionnaire before the session, after the first and the second teaching session. Teaching covered interrupted suturing, wound management, and administration of local aesthetic. Likert scores were used to collect feedback. Results: Total 24 third year medical students attended the two teaching sessions. 100% either agreed or strongly agreed the classroom teaching was useful, compared to 75% for the escape room. 67% either agreed or strongly agreed that escape room style teaching is a better learning method than traditional teaching. Although, 79% either agree or strongly agree that escape room style teaching is a useful adjunct to the traditional teaching. 100% either agree or strongly agree that this teaching will improve their clinical practice. Conclusions: Traditional classroom-based teaching is a more useful form of teaching compared to the escape room. Although escape room teaching is a useful adjunct to the current common form of classroom based surgical teaching.